Most bicarbonate secretion by Calu‐3 cells is mediated by CFTR and independent of pendrin. Issue 5 (13th March 2018) - Huang, Junwei; Kim, Dusik; Shan, Jiajie; Abu‐Arish, Asmahan; Luo, Yishan; Hanrahan, John W.
Abstract: Bicarbonate plays an important role in airway host defense, however, its transport mechanisms remain uncertain. Here we examined the relative contributions of the anion channel CFTR (cystic fibrosis transmembrane conductance regulator, ABCC7) and the anion exchanger pendrin (SLC26A4) to HCO3 − secretion by the human airway cell line Calu‐3. Pendrin and CFTR were both detected in parental Calu‐3 cells, although mRNA and protein expression appeared higher for CFTR than for pendrin. Targeting pendrin transcripts with lentiviral shRNA reduced pendrin detection by immunofluorescence staining but did not alter the rates of HCO3 − or fluid secretion, HCO3 − transport under pH‐stat conditions, or net HCO3 − flux across basolaterally permeabilized monolayers. Intracellular pH varied with step changes in apical Cl − and HCO3 − concentrations in control and pendrin knockdown Calu‐3 cells, but not in CFTR deficient cells. Exposure to the proinflammatory cytokine IL‐4, which strongly upregulates pendrin expression in airway surface epithelia, had little effect on Calu‐3 pendrin expression and did not alter fluid or HCO3 − secretion. Similar results were obtained using air–liquid interface and submerged cultures, although CFTR and pendrin mRNA expression were both lower when cells were cultured under submerged conditions. While the conclusions cannot be extrapolated to other airway epithelia, the present results demonstrate that most HCO3 − secretion by Calu‐3 cells is mediated by CFTR. Abstract : Bicarbonate secretion by epithelial cells plays an important role in airway host defense, however, the pathways for secretion remain uncertain. The Calu‐3 cell line is a widely used model for secretion by submucosal gland serous cells. We show here that most bicarbonate secretion by Calu‐3 cells depends on the anion channel CFTR and is independent of the anion exchanger pendrin.